Analisis Kepuasan atas Fitur Layanan dan Citra Merek serta Pengaruhnya terhadap Pengguna Aplikasi Mobile Payment DANA - Erin Rahma Nisa; Tri Kurniawati (Jurnal Salingka Nagari, 2023)
The objective of this study is to analyze the impact or satisfaction on service features and brand image on consumer loyalty of mobile payment DANA. This is quantitative research. The data collection is used by using questionnaire. The samples of this study are 97 students in Universitas Negeri Padang. The results of this study show that: (1) Satisfaction of service features has a significant effect on the loyalty of Universitas Negeri Padang students in using DANA mobile payment application, (2) Brand image has a significant effect on the loyalty of Universitas Negeri Padang students in using DANA mobile payment application, (3) Satisfaction of service features and brand image have a significant effect on the loyalty of Universitas Negeri Padang students in using DANA mobile payment application.